PENGARUH TINGKAT PERTUMBUHAN, STRUKTUR AKTIVA, PROFITABILITAS, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PERUSAHAAN PERTAMBANGAN DI BEI - Deviani, Made Yunitri; Sudjarni, Luh Komang (E-Jurnal Manajemen, 2018)
Competition in the business world encourages financial managers to take decisions carefully, one of which decisions related to capital structure. This study aims to examine the effect of growth rate, asset structure, profitability, and liquidity on the capital structure of mining companies in Indonesia Stock Exchange period 2012-2015 period. This research uses associative design with quantitative approach. Capital structure is calculated by long term debt to equity ratio, asset structure by comparing current assets with fixed assets, profitability is calculated by return on equity, and liquidity is calculated by current ratio. The method used to determine the sample is purposive sampling method with sample size 23 companies. Data analysis technique used is multiple linear regression analysis. The results showed that partially significant growth rate negatively affect the capital structure, asset structure has a negative but not significant effect on capital structure, and profitability and liquidity have a significant negative effect on capital structure . Keyword: growth, asset structure, profitability, liquidity, capital structure